Disentangling human impact from natural controls of sediment dynamics in an Alpine catchment. Issue 14 (9th September 2019) - Stutenbecker, Laura; Costa, Anna; Bakker, Maarten; Anghileri, Daniela; Molnar, Peter; Lane, Stuart N.; Schlunegger, Fritz
Abstract: Human activities have increasingly strong impacts on the sediment dynamics of watersheds, directly, for example through water abstraction and sediment extraction, but also indirectly through climate change. This study aims at disentangling these impacts on natural sediment fluxes for the Borgne River, located in the Alps of southwest Switzerland, using two approaches: First, an assessment of contemporary sediment sources and their relative contribution to the sediment delivered to the catchment outlet is undertaken by geochemical fingerprinting and a mixing model. Second, a spatially distributed conceptual model of suspended sediment production and transfer is used to quantify the contribution of different portions of the catchment to the total sediment yield. The model describes the influence of hydroclimatic variables (rainfall, snowmelt, and ice melt), water diversions and reservoir trapping on the sediment yield accounting for the erodibility of the different land covers present in the catchment. The analysis of different scenarios based on this conceptual model aids the interpretation of the fingerprinting results and the identification of the most important factors controlling sediment fluxes. Although the conceptual model overestimates the contribution of the downstream source area and underestimates the contribution of the upstream source area, the results allow us to qualitatively assess the impacts of different drivers influencing the sediment yield at the catchment scale. The results suggest: (1) high sediment yield from the uppermost part of the catchment due to sediment delivery by glacial ice melt; (2) delayed sediment transfer from areas impacted by water abstraction; and (3) reduced sediment contribution from areas upstream of a major hydropower reservoir that intercepts and traps sediment. Although process (1) and processes (2) and (3) serve to counter one another, our study emphasizes that the relative impacts of Anthropocene climate change and human impacts on sediment delivery may be disentangled through multi‐proxy approaches. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : Combining sediment fingerprinting and a conceptual model to quantify sediment production and transfer, we investigate modern sediment sources in the Borgne, an Alpine basin strongly influenced by human activities. Results show that areas with significant glacial cover currently produce most sediment due to a recent increase in glacial melt, areas impacted by water management transfer sediment with a delay of c . four months, areas trapped by hydropower dams contribute less sediment than non‐trapped areas.